2019
DOI: 10.15407/spqeo22.04.470
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of interface interactions in core-shell nanocomposites of intrinsically conducting polymers

Abstract: In this mini-review, we address the importance of specific interactions in coreshell structures composed with intrinsically conducting polymers (ICPs) as a shell and various nanoparticles used as a core. These interactions that can appear during the polymerization process of corresponding monomers or in the course of subsequent treatments of already formed core-shell nanocomposites play a crucial role in determining their structure and unique physical properties. They also lead to significant differences in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(59 reference statements)
0
5
0
2
Order By: Relevance
“…It is well known that PAni's electrical structure is necessarily impacted by the variation in oxidation level. As a result, it was reported that the polaron band for phase PAni in the composites was narrower than that for unmodified PAni (matching to absorption spectra), and it continuously became better by increasing the concentration of TiO 2 NPs [53]. Mobility of produced carriers (polarons) along PAni chains results from this in turn [54].…”
Section: Electrical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…It is well known that PAni's electrical structure is necessarily impacted by the variation in oxidation level. As a result, it was reported that the polaron band for phase PAni in the composites was narrower than that for unmodified PAni (matching to absorption spectra), and it continuously became better by increasing the concentration of TiO 2 NPs [53]. Mobility of produced carriers (polarons) along PAni chains results from this in turn [54].…”
Section: Electrical Propertiesmentioning
confidence: 92%
“…As can be shown from the resistivity investigations, the concentration ratios of TiO 2 NPs (0, 20, 25 and 33%) have a major effect on the conductivity of the films formed, causing the conductivity to rapidly improve to 4.77, 5.34, 6.04, and 6.58 S/m, respectively. The TiO 2 NPs' physicochemical interactions with the PAni chains, which result in a change in the oxidation state, are the main source of this activity, that has previously been explored by others [53], [54]. It is well known that PAni's electrical structure is necessarily impacted by the variation in oxidation level.…”
Section: Electrical Propertiesmentioning
confidence: 98%
“…[12,13] However, while the former approach allows us to prepare the NCs with synergistic properties in limited cases, the latter one is more efficient due to a number of factors, in particular, the formation of intimate contacts and specific interactions between all components both of the polymerization mixture and of the prepared NCs. [14,15] Moreover, the size-dependent effects, known for ultrathin ICP films, can also be superimposed on the force field effects at the interface between the nanocomposite components. [16][17][18] Under these conditions, properties of an ICP layer/shell deposited on the surface of the substrate can differ significantly from the properties of a pure polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Under these conditions, properties of an ICP layer/shell deposited on the surface of the substrate can differ significantly from the properties of a pure polymer. [15,[19][20][21] We earlier showed that the doped poly(3-methylthiophene) (P3MT) in the nanostructured shells on the surface of the ferroelectric poly(vinylidene fluoride) (PVDF) particles had higher effective conjugation length, more regioregular molecular structure, improved intrachain packing order, and lower bipolaron/polaron ratio compared with the neat P3MT. [21] In such cases, properties of the ICP phase can depend on the thickness of its layer or particle size, as, for example, was shown for the NCs of polyaniline with multiwall carbon nanotubes (MWCNT).…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy for the next decade included theoretical consideration of new effects in low-dimensional semiconductor structures [7][8][9][10], establishment of new principles and approaches to create and study functionality of lasers and LEDS [11][12][13][14][15][16][17][18], clarification of some peculiarities in new hetero-and hybrid structures [19][20][21], application of sensor and photovoltaic cells [22][23][24][25][26][27], use of semiconductor, optic and quantum electronic devices in ecology, communications, renewable energetics and health care [28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%